Confronting conflict of interest. (November 2018) - Unknown
Recent news stories about conflict of interest in biomedical research have shaken up public and private institutions alike, but their focus was on clinical research. Amidst the renewed focus on conflicts of interest in clinical work, let's not disregard the fact that financial conflicts also pose a concern to basic and preclinical research.